ASPEK OPTIMISME SEBAGAI REALISASI NILAI NASIONALISME: Analisis Semiotika Lirik Lagu Garuda di Dadaku - Purnama, Sasmitaningtyas Citra; Wisudawanto, Rahmat; Anggitya, Paramastu Titis (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2014)
Nowdays, the improvement of nasionalism is needed. One of them is the pround feeling throught our national football. In motivation national football team player. It is needed to sing a song which has nasional theme. One of them is Garuda di Dadaku. This research is aimed to identify and to classify optimism aspects in Garuda di Dadaku and also to describe denotative and conotative meaning and also mitos based on those aspects. This rescach belongs to descriptive qualitative, the source of data is the lyrics of Garuda di Dadaku, where as data in this research in all of phrase which consist of optimism aspects. This research used semiotics analysis theory of Roland Barthes. The analysis was done throught three steps, namely denotation level, conotation level and mitos. The results of analysis shows that there are three optimism aspect in Garuda di Dadaku lyrics. There are permanensi, pervasivitas and personalisasi. Base on eleven data, the distribution to ward the aspect are 6 data consider as permanensi aspects, data classified as pervasivitas aspect and data categories as personalisasi aspect. Where as in mitos level data categories a two. Namely proud and pride.